TESTINGTHE USE OF A BASKOM AT THE MOUTH OF THE BUBU FOR LOBSTER(Cherax quadricarinatus) FISHING GEAR - Tamba, Riwaldi; Syofian, Irwandy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted on 11 -20Â October 2016 in districts Tanjung Raya (Like Maninjau). Materials and tools used in this research is a fish die as bait and atools that is used in the form of 3 units bubu material net funnel and 3 units bubu materials baskom funnel, boat as tools toward mounting points bubu. The methods used in this study is experiment methods where the study was to test the use of a baskom at the funnel of the bubu for lobster (Cherax quadricarinatus) fishing gear is done directly at the capture. Differences in the type of material does not affect the funnel bubu catches can be demonstrated on the real level of 0,01 t- hit (1,42) Ë t- tab (3,24). Therefore the average treatmant in said non-significant or not real.Then H0 meaning there is no influence of the type of materials funnel to catch lobster bubu.Keywords: Fishing gear, Material funnel Bubu, Danau Maninjau